Kualitas Manajemen Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien di Alia Hospital - Hutama Bagus Al Faqih; Hendi Trisandi; Nisrina Mauritania; Niswah Aryahiyyah Dhabithah; Swanti Novita (Comit: Communication, Information and Technology Journal, 2024)
Social interaction patterns and patient perceptions play an important role in describing the level of patient satisfaction with hospital services. This research aims to find out how the health services provided by Alia Hospital influence patient satisfaction. This research uses qualitative methods and literature study. The research approach used in this research is qualitative research using descriptive methods. Literature study is data collection that involves analysis of various sources such as books, literature, notes, journals, reports and data related to the problem being discussed. The variables in this research include reliability, responsiveness, assurance, empathy, and physical appearance of the service/tangible as well as patient satisfaction. The research results also show that patient satisfaction at Alia Hospital increases when the services provided are in accordance with the patient's needs and desires, and when health workers can communicate with patients well and show empathy